Numerical Monitoring of Natural Gas Distribution Discrepancy Using CFD Simulator - Vadim E. Seleznev (Journal of Applied Mathematics)
The paper describes a new method for numerical monitoring of discrepancies in natural gas supply to consumers, who receive gas from gas distribution loops. This method serves to resolve the vital problem of commercial natural gas accounting under the conditions of deficient field measurements of gas supply volumes. Numerical monitoring makes it possible to obtain computational estimates of actual gas deliveries over given time spans and to estimate their difference from corresponding values reported by gas consumers. Such estimation is performed using a computational fluid dynamics simulator of gas flows in the gas distribution system of interest. Numerical monitoring of the discrepancy is based on a statement and numerical solution of identification problem of a physically proved gas dynamics mode of natural gas transmission through specified gas distribution networks. The identified mode parameters should have a minimum discrepancy with field measurements of gas transport at specified reference points of the simulated pipeline network.